Interferon‐free treatment of chronic hepatitis C with faldaprevir, deleobuvir and ribavirin: SOUND‐C3, a Phase 2b study. (16th October 2014) - Zeuzem, Stefan; Dufour, Jean‐François; Buti, Maria; Soriano, Vicente; Buynak, Robert J.; Mantry, Parvez; Taunk, Jawahar; Stern, Jerry O.; Vinisko, Richard; Gallivan, John‐Paul; Böcher, Wulf; Mensa, Federico J.; et al.
Abstract Background & Aims The safety and efficacy of the interferon‐free combination of faldaprevir (NS3/A4 protease inhibitor), deleobuvir (BI 207127, non‐nucleoside polymerase inhibitor), and ribavirin in treatment‐naïve patients chronically infected with HCV genotype‐1 was explored. Methods SOUND‐C3 was a multicenter, open‐label Phase 2b study. Treatment‐naïve patients chronically infected with HCV genotype‐1a (IL28B CC genotype only; n = 12) and genotype‐1b (n = 20) were assigned to 16 weeks of treatment with faldaprevir 120 mg once daily, deleobuvir 600 mg twice daily, and weight‐based ribavirin. Patients with compensated liver disease, including cirrhosis, were eligible for inclusion in this study. The primary endpoint was sustained virological response 12 weeks after completion of therapy. Results Sustained virological response rates 12 weeks after completion of therapy were 17% and 95% in patients infected with HCV genotype‐1a and genotype‐1b respectively. All four patients with cirrhosis achieved sustained virological response 12 weeks after completion of therapy. The most frequently reported adverse events of at least moderate intensity were anaemia (16%), nausea, vomiting and fatigue (9% each). Three (9%) patients discontinued because of adverse events. Conclusions The interferon‐free regimen of faldaprevir, deleobuvir and ribavirin was efficacious in patients infected with genotype‐1b and generally well tolerated.